HUBUNGAN MOTIVASI ORANG TUA DENGAN KEMAMPUAN MENGENAL HURUF PADA SISWA KELAS B DI TK. AZHARIAH DESA SURO KECAMATAN MUARA BELITI KABUPATEN MUSI RAWAS - Lia Mardiyanti (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2017)
Kindergarten is one of the early childhood education institutions found in the formal education pathway. In accordance with the objectives of TK according to the laws of the Republic of Indonesia No. 20 of 2003 concerning the First National Education system CHAPTER VI article 28 paragraph 3 reads: